Identification of Digital Image Using Protein Folding and Unfolding Structure: An Efficient Approach for Image Authentication and Recovery using Fragile Watermarking (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The past decade has witnessed an explosion-like storm of digitization in the life of many and its impact has its own reasons and consequences in other matters. Internet-connection able PCs have enabled the mobility of information and made convenient the carriage of digitized property closer to home than ever before. With the growing use and need of digital multimedia technology the security of multimedia information like audio, video, text and image have become a major concern. Integrity of image information is important especially when this type of data is used for authentication purpose e.g. medical diagnosis or court evidence. This is an interesting challenge and this is probably why so much attention has been drawn toward the development of digital information protection schemes. Many approaches are possible to protect visual data, digital watermarking is probably the one that has received most interest. The idea of fragile watermarking of images is to embed information data within the image with an insensible form for human visual system but in a way that protects from attacks such as intentional or unintentional alteration in extensive content of the digital image. The goal is to produce an image that looks exactly the same to a human eye but still allows its positive identification in comparison with the owner’s key if necessary. To cover the same objective this work propose an efficient image authentication and recovery approach using block wise fragile watermarking.